THE APPLICATION OF PSAK 101 IN THE FINANCIAL STATEMENTS OF KSPPS BMT AL FATTAH - Widi Amelia Sari; Lily Wahyuni; Rita Dwi Putri (SEAN Institute, 2023)
PSAK 101 is a PSAK that regulates the presentation of Islamic financial statements. This research was conducted to know how the application of PSAK 101 in the financial statements of KSPPS BMT Al Fattah. In this study, qualitative descriptive research methods were used. The data collected is obtained through data collection techniques based on observation, interviews, documentation, and literature research. The results concluded that KSPPS BMT Al Fattah presented only the statement of financial position, income statement, and cash flow statement but the report presented has not applied PSAK 101 due to incomplete presentation of the report and there are errors in the report presented both in terms of naming and recognition. The reason for only three types of financial statements presented by KSPPS BMT Al Fattah is that BMT still does not understand the applicable standards. The two reports that have been presented are considered to have met the information needs of the BMT Al Fattah KSPPS. However, over time BMT Al Fattah also continues to improve the quality of existing experts and continues to utilize technology in assisting the presentation of financial statements by existing guidelines.